The Use of Social Media In Building the Political Image of Budi and Agis in the 2024 Serang City Elections - Asty Dina Mardina (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the strategic utilization of social media platforms in constructing the political image of Budi Rustandi and Nur Agis Aulia during the 2024 Serang City Election. Employing an empirical qualitative approach with an instrumental case study design, this inquiry analyzes how digital campaign operations cultivate political branding and manage candidate impressions among young voters. Primary data were gathered through semi-structured interviews with key campaign actors and targeted youth demographics, supplemented by non-participant observation of official social media repositories. The findings reveal that Instagram and TikTok were deployed in a highly differentiated manner to maximize algorithmic reach and validate candidate credibility. By projecting a carefully curated balance between legislative competence and grassroots populist values, the campaign generated significant cognitive alignment within the youth electorate. Crucially, the final results demonstrate that while digital communication offers immense cost efficiency in building widespread political visibility, actual electoral conversion relies on the strategic integration of virtual image formation and physical network mobilization.